Prevention of stricture recurrence following urethral internal urethrotomy: routine repeated dilations or active surveillance? - Tian, Ye; Wazir, Romel; Wang, Jianzhong; Wang, Kunjie; Li, Hong (Urology Journal, 2016)
Strictures of the urethra are the most common cause of obstructed micturition in younger men and there is frequent recurrence after initial treatment. Currently, routine repeated dilations, including intermittent self-catheterisation (ISC) are prescribed by urologists to prevent urethral stricture recurrence. There is, however, no high level evidence available supporting the effectiveness of practicing these painful techniques. Balancing efficacy, adverse effects and costs, we hypothesize that active surveillance is a better option for preventing stricture recurrence as compared with routine repeated dilations. However, well designed, adequately powered multi-center trials with comprehensive evaluation are urgently needed to confirm our hypothesis.